Minor pilins are involved in motility and natural competence in the cyanobacterium Synechocystis sp. PCC 6803 - Oeser, Sabrina; Wallner, Thomas; Schuergers, Nils; Bučinská, Lenka; Sivabalasarma, Shamphavi; Bähre, Heike; Albers, Sonja-Verena; Wilde, Annegret (Molecular microbiology, 2021)
Cyanobacteria synthesize type IV pili, which are known to be essential for motility, adhesion and natural competence. They consist of long flexible fibers that are primarily composed of the major pilin PilA1 in Synechocystis sp. PCC 6803. In addition, Synechocystis encodes less abundant pilin-like proteins, which are known as minor pilins. In this study, we show that the minor pilin PilA5 is essential for natural transformation but is dispensable for motility and flocculation. In contrast, a set of minor pilins encoded by the pilA9-slr2019 transcriptional unit are necessary for motility but are dispensable for natural transformation. Neither pilA5-pilA6 nor pilA9-slr2019 are essential for pilus assembly as mutant strains showed type IV pili on the cell surface. Three further gene products with similarity to PilX-like minor pilins have a function in flocculation of Synechocystis. The results of our study indicate that different minor pilins facilitate distinct pilus functions. Further, our microarray analysis demonstrated that the transcription levels of the minor pilin genes change in response to surface contact. A total of 122 genes were determined to have altered transcription between planktonic and surface growth, including several plasmid genes which are involved exopolysaccharide synthesis and the formation of bloom-like aggregates.
Keywords: Sequence Deletion; Synechocystis; sekvenční delece; mikročipová analýza; Bacterial Proteins; surface acclimation; Fimbriae, Bacterial; Fimbriae Proteins; cyanobacteria; Amino Acid Sequence; Bacterial Physiological Phenomena; proteiny fimbrií; regulace genové exprese u bakterií; stanovení celkové genové exprese; Gene Expression Profiling; type IV pili; bakteriální fimbrie; bakteriální proteiny; Microarray Analysis; sekvence aminokyselin; natural competence; minor pilin; fyziologie bakterií; Gene Expression Regulation, Bacterial